Սոցիալ–տնտեսական և ներքաղաքական ճգնաժամը Սիրիայում 1980-ական թթ. առաջին կեսին - Ղարիբջանյան, Գևորգ («Զանգակ - 97»)
Since the early 1980's, the economy of Syria has faced several main challenges. Among the socio-economic difficulties were the sharp decrease in oil prices on the international market in the early 1980's and the resulting reduction of aid privided to Syria by the rich oil-producing Arab countries. Another problem was the drop in the mid 1980's of the cotton prices on the international market, which was a hard blow for Syria. where cotton has been an important export commodity. In the Mid 1980's remittences home from Syrians working abroad also redueed almost in half. In order to overcome the difficulties Syria continued the Cooperation with Western and especially American oil companies.
Keywords: Պատմություն; Տնտեսություն; Սիրիա